THE FORMULATION OF TASTE AND VALUE IN AMERICAN ACTION-SPY MOVIES: AN ANALYSIS OF THE BOURNE SAGA - Muchammad Sofyan Firmansyah (Universitas Gadjah Mada, 2017)
The popularity of Hollywood action movies is undisputed, especially the ones related to espionage. The movies such as the 007 series and Mission: Impossible series are best known as successful action-spy movies as they are always considered the top blockbuster movies. However, the start of the release of The Bourne movies in 2002 changed audiences’ perspectives toward the depiction of espionage as commonly shown in 007 and Mission: Impossible. Four of The Bourne movies that consist of The Bourne Identity (2002), The Bourne Supremacy (2004), The Bourne Ultimatum (2007), and The Bourne Legacy (2011) are used as the object of this research. Furthermore, the different depictions of espionage in The Bourne movies successfully reached the attention of action-spy audiences. Many audiences from throughout the world expressed their feelings after watching these movies on the movie review site as IMDb.com. The audiences’ responses toward the different portrait of espionage that are presented in the movies may depend on the taste of those audiences with regards to the depictions inside the movies that may present certain American values as the narrative of the movies concerns an American named Jason Bourne. There are two goals of this research. The first is to reveal whether there is any relation between audiences’ taste and the values depicted in film whether these film are products of popular culture or not. The second is to know how these movies mold the American values in their narrative to appeal to the desire of audiences. This research is conducted under the American studies discipline, especially the paradigm of transnational American Studies. Furthermore, some theories are employed as tools to analyze the object in order to achieve the goal of this research. Conducted as qualitative research, books, movies, articles, and videos related to the focus of this research are used as supporting data.Keywords: The Bourne, Audience, Taste, Value.